Determination of fumonisin B1 and B2 in corn and corn-based products in Turkey by high-performance liquid chromatography - (:unkn) unknown (My University, 2001)
The purpose of this study was to investigate fumonisin B1 (FB1)- and B2 (FB2)-contaminated corn and corn-based products consumed especially by the Turkish population. FB1 and FB2 were detected using high-performance liquid chromatography with fluorescence detection. The total number of commercially available corn and corn-based product samples analyzed in this research was 82. The recoveries were found to be 94.4 +/- 4.62% and 86.5 +/- 4.86% for cornmeal spiked with known amounts of FB1 and FB2 (1 ppm), respectively. The minimum detectable amount for the o-phthaldialdehyde derivatives of FB1 and FB2 were 1 ng and 5 ng, respectively. Detected levels of FB1 were between 0.25 ppm and 2.66 ppm in 25.6% of the samples, and detected level of FB2 in a single cornmeal sample was 0.55 ppm.
Keywords: Turkey; Sensitivity and Specificity; Food Contamination; Chromatography, High Pressure Liquid; Fluorescence; Fumonisins; Zea mays; Carboxylic Acids; Carcinogens, Environmental; Mycotoxins